Structural and metabolic brain abnormalities in preclinical cerebral autosomal dominant arteriopathy with subcortical infarcts and leucoencephalopathy. Issue 1 (1st October 2008) - Stromillo, M L; Dotti, M T; Battaglini, M; Mortilla, M; Bianchi, S; Plewnia, K; Pantoni, L; Inzitari, D; Federico, A; De Stefano, N
Abstract : Objective: To assess, by using quantitative MRI metrics, structural and metabolic brain abnormalities in subjects with preclinical cerebral autosomal dominant arteriopathy with subcortical infarcts and leucoencephalopathy (CADASIL). Background: Brain MRI abnormalities have been occasionally reported in preclinical CADASIL subjects. However, very little is known as to when the brain tissue damage starts to accumulate, what brain regions are primarily involved and whether the brain damage is significant in subjects who have no overt clinical manifestations of the disease. Methods: Twelve subjects (mean age 40 years; range 26–55 years; males/females 6/6) with genetically proven CADASIL and no clinical signs of the disease underwent conventional MRI and proton MR spectroscopic imaging ( 1 H-MRSI) to measure white matter (WM) lesion volume (LV), global and regional cerebral volumes, and WM levels of N-acetylaspartate (NAA) normalised to creatine (Cr). MR values were compared with those of 13 age- and sex-matched healthy controls. Results: All preclinical CADASIL showed WM lesions (range 0.2 to 26 cm 3 ). They were mostly distributed in the frontal and parietal regions, with the highest probability in the corona radiata. On 1 H-MRSI examination, NAA/Cr values were lower in preclinical CADASIL than in HC, particularly in the corona radiata (p<0.01). Normalised brain and cortical volumes were also lower in preclinical CADASIL than in HC (p<0.01), particularly in the frontal cortex. Conclusions: The pathological process occurring in CADASIL leads to damage of WM and neocortex much before the evidence of clinical symptoms. At this preclinical stage, this seems to take place prevalently in the frontal brain region.